Tanggung Jawab Negara dalam Pemenuhan Hak Atas Kesehatan Jiwa dihubungkan dengan Hak Asasi Manusia - Lefri Mikhael (Badan Strategi Kebijakan Hukum, 2022)
The frightening global situation due to the COVID-19 pandemic has caused various problems related to health conditions, including mental health crisis. The fulfillment of mental health as part of human rights is a logical consequence of the ratification of the International Convention on Economic, Social, and Cultural Rights by Indonesia. The State as the duty bearer is obliged to fulfill, protect and respect every existing human right, including the right to health. This research aims to examine the relation between the regulation of the human right to health and the right to mental health and the State's responsibility through the implementation of the fulfillment of mental health rights. The method used is doctrinal legal research. The result of the analysis found that the mental health right is an integrated part of the right to health with the main responsibility for fulfilling it is the State's obligation according to the current constitution. There are several forms of substantial efforts by the State to fulfill it. Those implementation forms require efforts to increase and equalize facilities by the State to fulfill mental health right maximally.